Praxeologie in der Historischen Bildungsforschung. Möglichkeiten und Grenzen eines Forschungsansatzes - Hoffmann-Ocon, Andreas; De Vincenti, Andrea; Grube, Norbert (transcript Verlag, 2020)
Praxeology in Historical Education Research. Possibilities and Limitations of a Research Approach: How may practices in historical-educational contexts be explored? The contributors - education researchers, historians, ethnologists and sociologists - take an interdisciplinary approach to the question of the possibilities and limitations of praxeology. Their main focus is on pedagogically relevant routines and rituals as well as on self-will and practice linkages. These are traced by means of extensive source analyses, taking into account teachers' colleges, studies, schools, associations and kindergartens. As the variety of practices and contexts is linked with pragmatic explorative deliberations, praxeology is exemplified and discussed in its various facets.